أثر التسويق الداخلي على الروح المعنوية للعاملين ودور الصحة التنظيمية والاندماج الوظيفي في جهاز تنظيم شؤون السودانيين بالخارج - د. محمود عبد المعطي هاشم عبد الحميد (جامعة الشيخ عبدالله البدري, 2023)
المستخلص: هدفت الدراسة إلى بيان أثر التسويق الداخلي على الروح المعنوية للعاملين ودور الصحة التنظيمية والاندماج الوظيفي في جهاز تنظيم شؤون السودانيين بالخارج، واستخدمت المنهج الوصفي التحليلي والمنهج التاريخي، وتمثلت عينة الدراسة في الإداريين والموظفين بعدد (91) مفردة، وتوصلت الدراسة إلى توسط الاندماج الوظيفي في العلاقة بين التسويق الداخلي والروح المعنوية للعاملين بتأثير غير مباشر (0.604). وتُعدِّل الصحة التنظيمية العلاقة بين التسويق الداخلي والروح المعنوية للعاملين بقيمة تغير في معامل التحديد (0.063). وأوصت الدراسة بضرورة توعية القادة بالجهاز بأهمية التسويق الداخلي والصحة التنظيمية في تحقيق الاندماج الوظيفي لتنعكس على رفع مستوى الروح المعنوية. Abstract: The study aimed to investigate the influence of Internal Marketing on Employees Morale and The Role of Organizational Health & Job Engagement at The Organization for Regulating Sudanese Affairs Abroad. The study followed the descriptive analytical method & historical method. The study sample consist of (91) Managers and Employees. As The study reached a job engagement mediates the relationship between internal marketing and employees morale with an Indirect Effect of (0.604) and organizational health moderates the relationship between internal marketing and employees morale with a change in the coefficient of determination (0.063). The study recommended there is a need to increase leaders at The Organization for Regulating Sudanese Affairs Abroad awareness in the importance of internal marketing and organizational health in achieving job engagement to reflex on increase level of employees morale.
The Influence of Internal Marketing on Employees Morale and The Role of Organizational Health & Job Engagement at The Organization for Regulating Sudanese Affairs Abroad